2020
DOI: 10.1093/ndt/gfaa083
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic retroperitoneal fibrosis: an update for nephrologists

Abstract: Idiopathic retroperitoneal fibrosis (IRF) is a rare condition characterized by the development of a peri-aortic and peri-iliac tissue showing chronic inflammatory infiltrates and pronounced fibrosis. Ureteral entrapment with consequent obstructive uropathy is one of the most common complications of IRF, which can lead to acute renal failure and, in the long term, to varying degrees of chronic kidney disease. IRF may be isolated or develop in association with autoimmune diseases (e.g. Hashimoto’s thyroiditis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 82 publications
4
41
0
9
Order By: Relevance
“…Some typical computed tomography (CT) and/or magnetic resonance imaging (MRI) findings of IRPF have been described 15 although they are not disease-specific, and a comprehensive approach considering clinical and radiological correlations is still needed. Compared with the findings in secondary RPF (eg malignancy), the typical CT/MRI findings of IRPF include soft tissue masses surrounding anterolaterally a infrarenal abdominal aorta (as opposed to malignant RPF which usually extends to a suprarenal aorta) and/or proximal common iliac arteries without displacing them, a tendency for the ureters to deviate medially (as opposed to lateral displacement by malignant RPF), and absence of infiltration into muscle or bone ( Figure 1 ).…”
Section: Imaging Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some typical computed tomography (CT) and/or magnetic resonance imaging (MRI) findings of IRPF have been described 15 although they are not disease-specific, and a comprehensive approach considering clinical and radiological correlations is still needed. Compared with the findings in secondary RPF (eg malignancy), the typical CT/MRI findings of IRPF include soft tissue masses surrounding anterolaterally a infrarenal abdominal aorta (as opposed to malignant RPF which usually extends to a suprarenal aorta) and/or proximal common iliac arteries without displacing them, a tendency for the ureters to deviate medially (as opposed to lateral displacement by malignant RPF), and absence of infiltration into muscle or bone ( Figure 1 ).…”
Section: Imaging Findingsmentioning
confidence: 99%
“…Such renal involvement in RPF can lead to not only acute kidney injury (AKI) but also chronic kidney disease (CKD) including renal atrophy or even end-stage renal disease (ESRD). 15 Accordingly, the epidemiology, pathophysiology, clinical features, and management of RPF need to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Idiopathic retroperitoneal fibrosis (IRF) is a rare disease characterized by the development of peri-aortic and peri-iliac tissues showing chronic inflammatory infiltrate and pronounced fibrosis. 1 To the best of our knowledge, this is the first report of GPP complicated with IRF successfully treated with the anti-tumor necrosis factor (TNF)α antibody infliximab.…”
Section: Generalized Pustular Psoriasis Complicated With Idiopathic Retroperitoneal Fibrosis Successfully Treated With Infliximabmentioning
confidence: 98%
“…with autoimmune disease including psoriasis. 1 Interleukin-17 could present the link between T-cell activation and psoriasis and the trigger of the fibrosing periaortitis ultimately leading to IRF. 2 A recent study on 113 IRF patients found that 21% of them had high IgG4 levels at diagnosis.…”
Section: Idiopathic Retroperitoneal Fibrosis May Develop In Associationmentioning
confidence: 99%
“…IgG4-RD RF benefits of the same treatments already described. Notably, recent reports of MMF and RTX treatment in RF show efficacy whether or not it is a manifestation of IgG4-RD (60,61). Some conditions, such as smoking habit, AKI at diagnosis, ANA positivity and lumbar pain, are associated to relapse, and all these factors represent a negative prognostic combination for renal outcome (62).…”
Section: Treatment and Follow-upmentioning
confidence: 99%